Initial Experience of Cutaneous Continent Urinary Diversion by Modified Penn Pouch Technique: Is It More Expedient than Ileal Conduit? - Belal, Md Towhid; Zico, Nahid Rahman; Habibullah, ABM; Bhuiyan, AKM Musa; Chowdhury, Md Shafiqul Alam (Bangladesh Journal of Urology, 2023)
Introduction: In the current clinical practice, following cystectomy, either due to malignant or benign pathologies, the most common urinary diversion is in the form of ileal conduit. Quality of life is markedly decreased in patients with ileal conduit as they have to carry an external appliance with the poorest self-images that significantly reduce the desires of all forms of physical contact (sexual and non-sexual). Here we describe the initial experience of cutaneous continent urinary diversion following cystectomy that provides the patients with an external appliance-free life with good functional outcomes of the reservoir. Methods : The hospital records of 6(six) patients during a period of 5 months were reviewed retrospectively who underwent cutaneous continent urinary diversion in Dhaka Medical College Hospital, Dhaka and Center for Kidney Diseases & Urology Hospital, Dhaka. Out of 6 (six) patients, 5(five) underwent radical cystectomy for muscle-invasive bladder cancer, and 1(one) patient underwent simple cystectomy for exstrophy bladder. For the creation of the reservoir modified Penn pouch technique was applied, and the appendix was used as a catheterizable cutaneous stoma for the continent mechanism. A peri-operative and short periods of postoperative outcomes, including complications, quality of life assessment, continence and ability to empty the reservoir by selfcatheterization, was recorded. Results : Among the 6 (six) patients, 5 (five) cases were following radical cystectomy for muscle-invasive bladder cancer, and 1 (one) was following simple cystectomy for exstrophy bladder. After a median follow-up of 6 weeks, the continence rate was 100%. All patients (100%) could empty the neo-bladder by self-catheterization every 4-8 hours. Patients were highly satisfied with this stoma as they could avoid external appliances. Conclusion : Cutaneous continent urinary diversion is a successful method of neobladder construction following cystectomy for urinary bladder malignancy or severe functional and anatomical urinary bladder abnormalities with excellent functional outcomes. It needs skilled surgical techniques, and the decision on this method used should depend upon the indications and contraindications of surgery like renal functional status, patient anatomy, the physical and physiological condition of the patients and personal choice. Bangladesh J. Urol. 2022; 25(1): 7-13